Organizational characteristics associated with high performance on quality measures in pediatric primary care: A positive deviance study. Issue 3 (21st July 2021) - Goff, Sarah L.; Mazor, Kathleen M.; Priya, Aruna; Moran, Michael; Pekow, Penelope S.; Lindenauer, Peter K.
Abstract : Supplemental digital content is available in the text. Abstract : Background: Pediatric health care quality in the United States varies, but the reasons for variation are not fully understood. Differences in pediatric practices' organizational characteristics, such as organizational structures, strategies employed to improve quality, and other contextual factors, may contribute to the variation observed. Purpose: To assess the relationship between organizational characteristics and performance on clinical quality (CQ) and patient experience (PE) measures in primary care pediatric practices in Massachusetts. Methodology: A 60-item questionnaire that assessed the presence of selected organizational characteristics was sent to 172 pediatric practice managers in Massachusetts between December 2017 and February 2018. The associations between select organizational characteristics and publicly available CQ and PE scores were analyzed using analysis of variance; open-ended survey questions were analyzed using qualitative content analysis. Results: Eighty-six practices (50.0%) responded; 80 (46.5%) were included in the primary analysis. Having a quality champion ( p = .03), offering co-located specialty services (e.g., behavioral health; p = .04), being a privately owned practice ( p = .04), believing that patients and families feel respected ( p = .03), and having a lower percentage of patients (10%–25%) covered by public health insurance ( p = .04) were associated with higher CQ scores. Higher PE scores were associated with private practice ownership ( p = .0006). Qualitative analysis suggested organizational culture and external factors, such as health care finance, may affect quality. Conclusions: Both modifiable organizational practices and factors external to a practice may affect quality of care. Addressing differences in practice performance may not be reducible to implementation of changes in single organizational characteristics. Practice Implications: Pediatric practices seeking to improve quality of care may wish to adopt the strategies that were associated with higher performance on quality measures, but additional studies are needed to better understand the mechanisms behind these associations and how they relate to each other.